1997
DOI: 10.1016/s0022-5347(01)64944-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Multi-Drug Resistance Associated Protein and P-Glycoprotein in Patients with Bladder Cancer

Abstract: Multi-drug resistance associated protein as well as P-glycoprotein mediated multi-drug resistance may be induced after chemotherapy for bladder tumors. However, the presence of P-glycoprotein before chemotherapy does not predict clinical outcome in patients with bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…The association between ABC transporters with bladder cancers was previously established. Recent studies have reported the overexpression of ABC transporters in chemotherapeutic patients with bladder cancer (32,49). CEBPD is also responsive to stimuli involving the activation of either p38 MAPK or STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…The association between ABC transporters with bladder cancers was previously established. Recent studies have reported the overexpression of ABC transporters in chemotherapeutic patients with bladder cancer (32,49). CEBPD is also responsive to stimuli involving the activation of either p38 MAPK or STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of any report describing mevalonate pathway overactivation in bladder cancer. In view of the limited therapeutic efficacy of current chemotherapeutic regimens [6] and the inability to explain the intrinsic and acquired urothelial carcinoma doxorubicin resistance by increased drug efflux alone [16][17][18][19], our finding calls for a more intense investigation of the function of this pathway in bladder cancer. In particular, if mevalonate pathway activation should be a critical factor in bladder cancer development and therapy resistance, it would offer a novel pharmacological target.…”
Section: Discussionmentioning
confidence: 99%
“…Their molecular analysis yielded an enhanced drug efflux as a major chemoresistance mechanism, either alone [10][11][12] or in association with a partial or complete loss of the therapeutic target, DNA topoisomerase II [13,14], or with a concomitant activation of antiapoptotic signalling pathways [15]. The analysis of clinical tumours, while corroborating the clinical significance of increased expression of drug efflux pumps like ABCB1 (MDR-1) or ABCC1 (MRP), suggested nevertheless that this is unlikely to represent the only resistance mechanism [16][17][18][19]. Here, we describe the establishment of a new cell culture model of doxorubicin resistance in bladder cancer and its molecular analysis.…”
Section: Introductionmentioning
confidence: 92%
“…For example, transcription of P-gp mRNA in tumor tissue of patients with metastatic osteosarcoma was rapidly enhanced in response to doxorubicin injection (59). Furthermore, multi-drug resistance and overexpression of P-gp in urinary cancer tissues were observed in urinary cancer patients after chronic anticancer chemotherapy by using anthracyclines, including doxorubicin and daunorubicin (38,60,61). On the other hand, cytotoxic agents, including doxorubicin (62), paclitaxel (63), and ETP (64), in conjunction with specific and/or potent inhibitors of P-gp such as cyclosporine or its analogues (PSC833 or GF120918) increased the residual levels of cytotoxic agents within tumor tissues in several clinical trials for patients with low sensitivity to anticancer chemotherapy, suggesting that resistance to these anticancer drugs was defeated.…”
Section: Alteration In the Expression And Function Of P-gp Induced Bymentioning
confidence: 99%